Strategi Program Hafiz Indonesia 2023 Di RCTI Dalam Memotivasi Peserta Menghafal Al-Quran - Audi Rizki Pangestu; Amin Shabana (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This thesis discusses the strategies carried out by the Indonesian Hafiz team at RCTI in motivating children to memorize the Al-Quran through television programs. The aim of this research is to analyze the planning, production, execution, evaluation and rating of the Hafiz Indonesia program and its relationship with children's motivation in memorizing the Al-Quran. The research method used is qualitative research with a descriptive approach. Data was collected through interviews with informants involved in the production of the Hafiz Indonesia program. The research results show that planning for the Hafiz Indonesia program was carried out by identifying the target audience and setting clear goals. Program production involves camera setup, lighting, sound, and coordination of actors or program participants. Program execution is carried out through promotions in TV advertising slots, social media, and direct information via WhatsApp groups. Program evaluation and monitoring is carried out regularly to monitor the quality of the content, community response and the resulting social impact. Program ratings are an indicator of public interest in this program. The conclusion of this research is that the strategy carried out by the Hafiz Indonesia team in motivating children to memorize the Al-Quran through television programs has proven to be effective. Good planning, efficient production, proper execution, regular evaluation, and close supervision are important factors in achieving these goals. The Hafiz Indonesia program is able to create a positive impact in society by increasing interest and understanding of the Al-Quran and strengthening religious deepening